Multimodal artistic metaphors: Research on a corpus of Sardinian art - Alice Guerrieri; Alice Guerrieri; Francesca Ervas; Elisabetta Gola (Frontiers in Psychology, 2023)
The study aims to define an artistic metaphor and highlight the multimodal properties of metaphors in artistic environments. In this research, an artistic metaphor has a relevant aesthetic purpose and it conveys beauty. Interpreting a metaphor in Sardinian art requires time for contemplation, however the cognitive effort of understanding the meaning of an artistic metaphor is rewarded by the delight of those who contemplate it. This metaphor has some characteristics in common with a visual metaphor but differs from other types of images that have been more extensively analyzed in the literature: it is difficult to establish a specific directionality, and consequently, it is not easy to recognize the target and source domains; the way it is expressed makes its interpretation and classification problematic at times. A proposal is presented in the paper to describe artistic metaphors according to universal macro-categories, inspired by the knowledge of Aristotelian and Kantian categories and by studies in the field of aesthetics: (1) time, (2) space, (3) decontextualization of stereotypes, and (4) fusion of forms. These categories are applied to a corpus of artworks by important artists in Sardinia to show that the visual, tactile, and auditory components of the pictures can boost an effective comprehension of figurative meaning. Results suggest that the multimodality of Sardinian artistic metaphors orients the observer toward original possibilities of learning and stimulates knowledge of the “submerged” wealth of symbols and archetypes that characterize insularity.